Synthesis and Characterization of Silicon Carbide-Carbon Composite (SiC-C) from Rice Husk Using Magnesiothermic Reduction - Solihudin Solihudin; Haryono MT (Jurnal Keramik dan Gelas Indonesia, 2021)
Silicon carbide (SiC) and SiC-C composite are non-oxide materials with good thermal properties so that they can be widely applied in industry. SiC can be synthesized by the magnesiothermic reduction method at a relatively lower temperature compared to carbothermal reduction. Rice husk charcoal has potential silicon and carbon content so that it can be used as a base material for the manufacture of SiC. This study aims to study the effect of calcination temperature in argon gas medium on the formation of SiC-C composites from rice husk charcoal reduction products using the magnesiothermic reduction method. The research methods include carbonization of rice husks, synthesis of SiC with magnesiothermic reduction method, calcination in argon gas medium for reduction products, and product purification, and product characterization. Calcination at the SiC-C composite formation stage was carried out at various temperatures of 700 and 1000 oC. The synthesized products were further characterized by FT-IR and XRD. Characterization by FT-IR showed that SiC was formed by magnesiothermic reduction method, while based on characterization by XRD, calcination at 700 oC in argon gas medium to the reduction product produced SiC-C composites with the highest content.